Transfer of quinolizidine alkaloids from hosts to hemiparasites in two Castilleja-Lupinus associations: analysis of floral and vegetative tissues - Adler, Lynn S.; Wink, Michael (Biochemical systematics and ecology, 2001)
Many hemiparasites, including several members of the Castilleja genus (Scrophulariaceae), obtain secondary compounds from their host plants. Both Castilleja miniata in subalpine Colorado and C. indivisa in central Texas have reduced herbivory when obtaining alkaloids from the hosts Lupinus argenteus and L. texensis (Fabaceae), respectively. However, pollinators were not deterred from visiting Castilleja parasitizing alkaloid-containing hosts. To determine if alkaloids are present in all tissues of plants parasitizing lupins, we analyzed floral tissue as well as leaves of both Castilleja species. Leaves, bracts, calices, corollas, gynoecium and nectar of both Castilleja species were examined for quinolizidine alkaloid presence using a Dragendorff reagent, and alkaloids were identified in vegetative tissue and nectar by capillary GLC and GLC-MS. Lupanine and alpha-isolupanine were the principal alkaloids in C. indivisa parasitizing L. texensis, while principal alkaloids of C. miniata parasitizing L. argenteus were 5,6-iso-dehydrolupanine, alpha-isolupanine, thermopsine, and 17-oxolupanine. Except for 17-oxolupanine, which was probably synthesized by biotransformation in the parasite, all other alkaloids correspond to those present in the host plants. Alkaloids were present in the leaves of both Castilleja species, and in the bracts, calices and gynoecium of some plants, but never in the corollas. Alkaloids from L. texensis and L. argenteus were not detected in nectar of either Castilleja species. The presence of alkaloids in leaves and outer floral tissue of both Castilleja species, but not nectar, may explain why alkaloid uptake and storage affected herbivores but not pollinators.